The giant stromatolite field at Santa Rosa de Viterbo, Brazil (Paraná Basin) – A new paleoenvironmental overview and the consequences of the Irati Sea closure in the Permian. (July 2018) - Callefo, F.; Arduin, D.H.; Ricardi-Branco, F.; Galante, D.; Rodrigues, F.; Branco, F.C.
Abstract: The city of Santa Rosa de Viterbo, São Paulo State, Brazil, contains an important geological and paleontological site that is part of the Paraná Basin and presents one of the most significant records of Permian microbial life of southwestern Gondwana: the giant stromatolite field, with structures reaching 3 m high and 6 m wide. This work proposes a new overview of the paleoenvironment, focusing on the growth and development of microbial mats and microbialites. The characterization and association of nine facies were performed: intraformational breccia with wackestone matrix, intraformational breccia with grainstone matrix, packstone, wackestone, microbial mats, peloidal wackestone, laminated peloidal wackestone, laminated peloidal packstone and stromatolites. Four lithologic logs were correlated and used to interpret the history of the establishment of microbial communities during the episode of the Irati Sea closure. Field studies were carried out, thin sections were analyzed, and techniques such as SEM/EDS and Raman spectroscopy were applied for compositional analysis and to aid in the identification of associated fossils. This moment in the Paraná Basin's evolution was important due to the noteworthy increase in rates of organic matter deposition and the significant proliferation of microbial life brought about by the closure of the Irati Sea. One hypothesis is that there was more than one attempt to establish microbial communities during the paleoenvironmental evolution, and success was achieved only after a decrease in water depth and energy of the depositional system, as well as after an increase in salinity. As a result of a reconfiguration of paleogeography in the Gondwana supercontinent, the closure of the Irati Sea significantly affected the development and establishment of microbial communities, which gave rise to extensive microbialitic structures such as those at Santa Rosa de Viterbo. Highlights: These stromatolites are result of continental changes during the Gondwana drift. Irati Sea closure increased salinity and made it possible the microbial growth. There was more than one attempt of microbial mat establishments.